Effect of Aqueous Extract of Melia azedarach on the some Biochemical Parameters in the Liver Extract of Infected Mice by Lieshmania donovani - Ibrahim Fatah Al-Harmni , Kawther; Ismail AL-Khan, Hussain; Ibrahim Fattohy, Zohair (Diyala Journal of Medicine, 2019)
This study was designed to examine the effect of combined drugs (pentostam and allopurinol) 20mg / kg and 20,40,60,80 and 100 mg / kg of the aqueous fruit extract of M. azedarach on infected mice for 10,15, and 20 days to determine their effect on some marker enzymes such as aspartate amino transferase ( AST ) , alanine amino transferase ( ALT ) , alkaline phosphatase ( ALP ) , lactate dehydrogenase ( LDH ) and the biochemical parameters like glucose , cholesterol and total protein, The present result showed a significant decrease of the two enzymes (AST and ALT) and significantly increased in (ALP and LDH) acivity in comparison with the enzyme activities in the liver of non– infected mice (con– ve). Where as the treated mice with 40 – 100mg / kg of aqueous fruit extract of the plant caused elevation in the activity of the (AST and ALT) and declining in (ALP and LDH ) activity when compared with infected non – treated mice ( con+ ve) after 10 ,15 and 20days post infection . The results also showed, non – significant differences in the glucose and cholesterol concentrations in infected mice in comparison with the non – infected mice. The treated mice with 20 mg/ kg pentostam/ allopurinol and 40 – 100 mg / kg of aqueous fruit extract of the plant caused in significant elevation of the glucose and cholesterol concentrations in the liver of infected mice in comparison with (con+ ve) after 10 , 15 and 20 days post treatment , but the infection caused non – significant increased in the total protein in liver of mice in comparison with (con– ve) , the treated mice with 20mg / kg pentostam / allopurinol and 40–100 mg / kg from aqueous fruit extract M.azedarach caused decrease of total protein when compared with (cont+ ve) for 10 , 15 and 20 days post treatment .